2016
DOI: 10.1002/1873-3468.12349
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of Arabidopsis thaliana calmodulin7 and insight into its mode of DNA binding

Abstract: Edited by Richard CogdellCalmodulin (CaM) is a Ca 2+ sensor that participates in several cellular signaling cascades by interacting with various targets, including DNA. It has been shown that Arabidopsis thaliana CaM7 (AtCaM7) interacts with Z-box DNA and functions as a transcription factor [Kushwaha R et al. (2008) Plant Cell 20, 1747-1759Abbas N et al. (2014) Plant Cell 26, 1036-1052. The crystal structure of AtCaM7, and a model of the AtCAM7-Z-box complex suggest that Arg-127 determines the DNA-binding abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 45 publications
(59 reference statements)
1
9
0
Order By: Relevance
“…Arabidopsis calmodulin 7 contains a single Cys in its second EF hand, which corresponds to C384 in TPK2. The oxygen of the peptide chain of Cys forms a coordinated bond with Ca 2+ [21]. A similar interaction of the free Cys is also observed in guanylyl cyclase activator protein 1 belonging to the calmodulin superfamily [22].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Arabidopsis calmodulin 7 contains a single Cys in its second EF hand, which corresponds to C384 in TPK2. The oxygen of the peptide chain of Cys forms a coordinated bond with Ca 2+ [21]. A similar interaction of the free Cys is also observed in guanylyl cyclase activator protein 1 belonging to the calmodulin superfamily [22].…”
Section: Discussionsupporting
confidence: 52%
“…EF1 in TPK2 contains two Cys separated by two amino acids (Figure 3(a)), a unique feature that is not present in the EF hands of TPK1, 3, 4 and 5, KCO3, the TPK homologs. Some calmodulin homologs possess a single Cys that corresponds to C384 in TPK2, but lack the second Cys corresponding to C381 [20][21][22]. The conserved Cys participates in the interaction with Ca 2+ in calmodulin [21].…”
Section: Role Of Cys In Ef2 Of Tpk2mentioning
confidence: 99%
See 1 more Smart Citation
“… The canonical EF-hand. Ca 2+ coordination in the Ca 2+ binding loop-4 of Arabidopsis CaM7 (PDB CODE: 5A2H) [ 3 ]. W, water molecule.…”
Section: Figurementioning
confidence: 99%
“…One of the prerequisites for proteasomal degradation is the presence of an unstructured region in the substrate (Erales & Coffino, 2014;Jariel-Encontre, Bossis, & Piechaczyk, 2008). Structural analysis and interaction studies of CaM demonstrated that it displays high conformational flexibility and itself undergoes from disorder to order transition (Barbato, Ikura, Kay, Pastor, & Bax, 1992;Kumar, Mazumder, Gupta, Chattopadhyay, & Gourinath, 2016;Radivojac et al, 2006;Tidow & Nissen, 2013;Wall, Clarage, & Phillips, 1997). In this case, the CaM may take up favorable geometry to facilitate interaction and translocation into the proteasome.…”
Section: Discussionmentioning
confidence: 99%